Equestrian Trauma: Injury Patterns Vary among Age Groups. Issue 4 (April 2014) - Bilaniuk, Jaroslaw W.; Adams, John M.; DiFazio, Louis T.; Siegel, Brian K.; Allegra, John R.; LujáN, Juan J.; Durling-Grover, Renay; Pawar, Joanne; Rolandelli, Rolando H.; Németh, Zoltán H.
Patients with equestrian injuries were identified in the trauma registry from 2004 to 2007. We a priori divided patients into three groups: 0 to 18 years, 19 to 49 years, and 50 years old or older. There were 284 patients identified with equestrian-related trauma. Injury Severity Score for the three major age categories 0 to 18 years, 19 to 49 years, and 50 years or older, were 3.47, 5.09, and 6.27, respectively. The most common body region injured among all patients was the head (26.1%). The most common injuries by age group were: 0 to 18 years, upper extremity fractures; 19 to 49 year olds, concussions; and 50 years or older, rib fractures. Significant differences were observed among the three age groups in terms of percent of patients with rib fractures: percent of patients with rib fractures was 2, 8, and 22 per cent in age groups 0 to 18, 19 to 49, and 50 years or older, respectively. We found different patterns of injuries associated with equestrian accidents by age. Head injuries were commonly seen among participants in equestrian activities and helmet use should be promoted to minimize the severity of closed head injuries. Injury patterns also seem to vary among the various age groups that ride horses. This information could be used to better target injury prevention efforts among these patients.